Study of porous rubber pipes reinforced with waste tire fiber and pineapple leaf fiber for smart irrigation system - M Junpunya; B Ou-udomying; Taweechai Amornsakchai; Ittipol Jangchud (IOP Conference Series Materials Science and Engineering, 2022)
Abstract Global trend in waste management involves sustainable development for waste utilization according to the concept of circular economy. Wastes from worn-out tires have been known as a world problem and not yet to be resolved successfully. In this work, wastes from worn-out tires, i.e., ground tire rubber (GTR), reclaimed rubber (RR) and waste tire fiber (WTF) were used to produce reinforced porous rubber pipes as irrigation system for smart farming. Comparative study of porous rubber pipes reinforced with natural fibers (pineapple leaf fiber, PALF) was also carried out. The experiment was divided into 2 parts, i.e., porous sheets (model study) and extruded porous pipes. Compound samples were prepared by mixing GTR, RR, and natural rubber (NR) at a ratio of 60:20:20 (by weight) with other additives by using an internal mixer, then shaped into samples by using a compression molding machine (sheets) and a single-screw extruder (pipes). Samples were vulcanized by a hot air oven. Factors affecting sample properties were studied, such as, fiber types (WTF and PALF) and fiber loadings (0-15 phr). Properties of the samples were characterized, such as, mechanical properties, morphology, water permeability rate, and %diameter swell. It was found that tensile strength was increased up to an optimum point. Modulus (at 10% strain, M10) and hardness were increased with increasing fiber loading. However, %elongation at break had a trend to decrease. Morphologies of the composites made from both fibers were insignificantly different in fiber distribution. By adding the fibers, %diameter swell was clearly improved. Pipe samples were also tested in precision smart agriculture system. It can be proven that WTF and PALF can be used to reinforce the porous pipes and used as a watering device for precision irrigation system.
Keywords: Natural Fiber Reinforced Composites; Advanced Cellulose Research Studies; Geotechnical Engineering and Soil Stabilization